The Role of School Leadership in Supporting Teacher Creativity to Improve Student Learning Outcomes in SMK Negeri 1 Al-Mubarkeya Ingin Jaya - Rahmi Isra (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
The research objectives are to determine and analyze the role of principal leadership in increasing teacher creativity at SMK Negeri 1 Al-Mubarkeya Ingin Jaya and to find out and analyze teacher creativity in improving student learning outcomes at SMK Negeri 1 Al-Mubarkeya Ingin Jaya. This study used a qualitative approach using purposive sampling technique to determine informants and data collection techniques were carried out through observation, interviews and focus group discussions (FGD). The role of principal as education leader in increasing the creativity of teachers in State Vocational High School I Al-Mubarkeya Ingin Jaya, Aceh Besar District, still has several shortcomings. This can be seen from the indicators that the principal as an educator is still not maximal in guiding teachers to prepare learning tools. The principal as a supervisor is still not able to prepare a supervision program properly, because he does not do classification of problems and check the correctness of the problem. The implementation of supervision is still constrained by curriculum differences. The principal as a leader also still has shortcomings so that it has implications for the level of creativity guru in improving student learning outcomes. Teacher There are still those who have difficulty in formulating and classifying specific instructional goals to develop students' attitudes, knowledge, and skills.